Biofilm Formation of Agrobacterium tumefaciens on Abiotic Surface is Independent of Cellulose Synthesizing Gene - Tuladhar, Reshma (Nepal Journal of Science and Technology, 2015)
Surface attachment is indispensable in the process of biofilm formation in Agrobacterium tumefaciens, which has been attributed to the production of extracellular polysaccharide. Adherence of bacteria on the plant was expected to be strong with cellulose synthesis. However, its role in the biofilm formation on abiotic surface is not known. Biofilm cover-slip assay was carried to estimate the biofilm formation. Biofilm formation was not reduced by truncating ellulose synthesis gene. The celCD deleted strain produced biofilm slightly greater than normal strain NTL4 of A. tumefaciens. Besides, production of extracellular polysaccharide was not reduced in the cellulose gene deleted strain NTL4 celCD. Quantitative estimation showed increased exo-polysaccharide in celCD deleted strain. Abolishing the cellulose synthesis property by truncating the cellulose gene did not affect biofilm formation in abiotic surface. In fact cellulose might be repressing biosynthesis of other polysaccharides responsible in biofilm formation. DOI: http://dx.doi.org/njst.v15i2.12112 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 41-46